Etnozoologi Masyarakat Suku Singkil di Kabupaten Aceh Singkil, Dalam Memanfaatkan Hewan Sebagai Obat Tradisional - khaira, jariati; Setyoko, Setyoko; Teuku Hadi Wibowo Atmaja (Jurnal Biotek, 2024)
To find out what types of animals are used, the parts of the organs used, what diseases can be treated, and how the animals used by the Singkil tribe are processed. This research was carried out from May to June 2023, in the Singkil tribe community, Gunung Meriah sub-district in Rimo village, Lae Butar village, Sianjo-Anjo festive village, Labuhan Kera village, Tanjung Petik village, Penjahitan village, Cingkam village, Tunas Harapan village, Tanah Bara village, Gunung Lagan village, warangusan village, Seping Baru village, Sebatang village, Tambakkan village, Tanah Merah village, Suka Makmur village, Sangga Beru Silulusen village, Tulak'an village. The tools used are stationery, a camera and the range of questions that will be asked during the interview as well as the research materials, namely the animals used by the Singkil tribe community. Qualitative research method with descriptive research type, the population is Gunung Meriah sub-district and the sample for this research is 30 respondents from the Singkil tribe/people who know better (healers) consisting of 18 villages in Gunung festive sub-district. The research results were obtained based on interviews with 30 healers consisting of 18 different villages. It was found that there were 21 types of animals used which were grouped into 9 classes, namely mammals, aves, reptiles, citellata, insects, actinoptenygi, gastropods, amphibians and bilvavia. Animal organs used throughout the body are 47%, meat 24%, liver 9%, horns 5%, small intestine 5%, fine fur 5%, blood 5%. There are 16 diseases and the processing methods can be boiled, grilled, fried, pasted, rubbed, roasted, pounded/mashed, grilled and eaten straight away. The organs that are most used are throughout the body. Keywords: Ethnozoology, Singkil Tribe Community, Traditional